Routine Clinical Practice Treatment Outcomes of Eplerenone in Acute and Chronic Central Serous Chorioretinopathy - Fasler, Katrin; Gunzinger, Jeanne M.; Barthelmes, Daniel; Zweifel, Sandrine A. (Frontiers in Pharmacology, 2021)
Purpose To evaluate efficacy of eplerenone therapy versus observation on resolution of subretinal fluid (SRF) in patients with acute and chronic central serous chorioretinopathy (CSCR) in routine clinical practice. Methods Retrospective comparative case series of eyes diagnosed with CSCR treated with eplerenone or observation. Primary outcome measure was maximum height of SRF at 12 months. Secondary outcome was percentage of eyes with complete resolution of SRF, percentage of eyes with reduction of SRF ≥ 50%, and best corrected visual acuity (VA) at 12 months. Separate analysis was conducted for eyes with acute and chronic CSCR. Results Sixty-eight eyes of 60 patients (82% male) were included. Eleven of the 38 eyes with acute CSCR, and 7 of the 30 eyes with chronic CSCR, received eplerenone. Subretinal fluid decreased from baseline to 12 months in acute (287±221µm to 31±63µm) and chronic (148±134µm to 40±42µm) CSCR. Kaplan-Meier curves were similar for treated and observed eyes and COX regression analysis did not show a significant difference in SRF resolution in treated versus observed eyes (p=0.6 for acute, p=0.2 for chronic CSCR). Conclusion This routine clinical practice outcome study did not show evidence of efficacy of eplerenone on resolution of SRF in acute nor chronic CSCR.